2018
DOI: 10.1159/000492661
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Regional Citrate Anticoagulation in Albumin-Assisted Liver Dialysis for Extracorporeal Liver Support in Pediatric Patients

Abstract: Aims: To establish the safety and efficacy of regional citrate anticoagulation (RCA) for pediatric liver failure (LF) patients receiving extracorporeal liver support (ELS) with albumin-assisted dialysis. Methods: Retrospective review of pediatric LF patients receiving ELS from April 2014 to December 2016 at a tertiary children’s hospital pediatric intensive care unit. Demographic and ELS data collected by chart review. Citrate accumulation (CA) was defined as total calcium (mmol/L): ionized calcium (mmol/L) > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…RCA was found to be an effective and safe method of anticoagulation during albumin dialysis 21 . A commercial citrate solution, used (anticoagulation citrate dextrose solution‐A) for RCA, can also provide safe and effective anticoagulation for pediatric patients with liver failure during albumin‐assisted dialysis 22 . A recent study found that the cTPEc is safe and well‐tolerated, and it improves coagulation profile and liver function tests in critically ill liver disease patients, but the overall survival remains low (69%, 31/45) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…RCA was found to be an effective and safe method of anticoagulation during albumin dialysis 21 . A commercial citrate solution, used (anticoagulation citrate dextrose solution‐A) for RCA, can also provide safe and effective anticoagulation for pediatric patients with liver failure during albumin‐assisted dialysis 22 . A recent study found that the cTPEc is safe and well‐tolerated, and it improves coagulation profile and liver function tests in critically ill liver disease patients, but the overall survival remains low (69%, 31/45) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the probability of lter survival in the RCA group was 94% and in the heparin group 82% during Molecular Adsorbent Recirculating System therapy (P = 0.204) [12]. RCA provides safe and effective anticoagulation for pediatric liver failure patients requiring extracorporeal liver support with albumin-assisted dialysis [13].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that included 10 observational studies of 1241 patients with hepatic dysfunction undergoing RCA-CRRT showed no significant difference in plasma citrate levels in patients compared to those without hepatic dysfunction [ 60 ]. Several studies have shown that RCA can also be used safely in patients with renal failure after liver transplantation or in patients being treated with extracorporeal artificial liver support [ 61 63 ].…”
Section: Methodsmentioning
confidence: 99%